Answer:
hi
Step-by-step explanation:
Answer
Slope between two given points (1,3) and (2,7) is
m=
2−1
7−3
=4
Then perpendicular slope is m
1
=
4
−1
The line equation with this slope is given by
y=
4
−1
x+c.......(1)
Now, the above line passes through the point (−4,−3)
⇒−3=
4
−1
×(−4)+c
⇒c=−4
Therefore required line is 4y+x+16=0 (Substitute
′
c
′
in (1) and simplify)
First you grapgh 0,-3 then you follow the slope of going 4 up 5 to the right and contine up also on e-where it is 0,-3 you go down 4 and 5 to the left and contine that to make a straught line.
You can use the equation
![{(x + 14)}^{2} + {x}^{2} = {34}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20%2B%2014%29%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%3D%20%20%7B34%7D%5E%7B2%7D%20)
to find the lenth of the legs
x = leg 1
x + 14 = leg 2
Answer:
y = 18 and x = -2
Step-by-step explanation:
y = x^2+bx+c To find the turning point, or vertex, of this parabola, we need to work out the values of the coefficients b and c. We are given two different solutions of the equation. First, (2, 0). Second, (0, -14). So we have a value (-14) for c. We can substitute that into our first equation to find b. We can now plug in our values for b and c into the equation to get its standard form. To find the vertex, we can convert this equation to vertex form by completing the square. Thus, the vertex is (4.5, –6.25). We can confirm the solution graphically Plugging in (2,0) :
y=x2+bx+c
0=(2)^2+b(2)+c
y=4+2b+c
-2b=4+c
b=-2+2c
Plugging in (0,−14) :
y=x2+bx+c
−14=(0)2+b(0)+c
−16=0+b+c
b=16−c
Now that we have two equations isolated for b , we can simply use substitution and solve for c . y=x2+bx+c 16 + 2 = y y = 18 and x = -2
Answer:
itb would be 60
Step-by-step explanation:
thata my answer